English-Georgian Dictionary - Tinatin Margalitadze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
The paper deals with the main stages in the development of the English-Georgian lexicography from the 19th century till the present time. It gives a more detailed description of the Comprehensive English-Georgian Dictionary under the general editorship of Donald Rayfield, published in London in 2006 by the "Garnett Press".